Changes in income and welfare of rural households through diversification and migration in Vietnam perceptions from poor farming households - Paris, Thelma R.; Luis, Joyce (2010)
Poverty reduction is an important development target of Vietnam, a poor country with a low income per capita. GDP per capita for the year 2000 was USD 363 and reached USD 720 in 2006. This paper examines the social and economic changes brought about by diversification (monoculture to diversified farming systems) and migration from rural to urban areas. To assess the changes, formal and informal surveys were conducted and analyzed to complement the surveys using pretested structured questionnaires. For the diversification study, changes to income and welfare of households representing different socioeconomic categories were compared. For the migration study, income and welfare of households with and without migrants by production systems (rainfed and irrigated) were examined. Findings revealed that among clear households, diversification and migration increased income and improved household welfare and also resulted in gender-differentiated outcomes. Along with these changes, women's participation in farming and other productive activities (e.g. marketing and decision-making authority) increased. However, despite these changes, women were seldom included in research and development programs. This exclusion has led to unintended negative consequences of technologies on poor women and landless women. The results imply that research, development, and extension programs should provide men and women equal access to resources and support services to further improve womens' income and welfare.
Keywords: Migrations; Family income